Musik tradisi berkelanjutan untuk generasi muda Dayak Bahau - Bayu Arsiadhi Putra; Jonathan Irene Sartika Dewi Max; Yofi Irvan Vivian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Traditional music is an expression of hereditary culture that is owned by certain ethnic groups. The young Dayak Bahau generation is committed to preserving traditional music even though they have experienced modern life and live in big cities. However, conservation efforts are always carried out in monotonous ways, resulting in various obstacles that are beyond the control of this ethnic group. Therefore, it is necessary to carry out empowerment activities so that the maintenance and preservation of traditional music can be sustainable. An understanding of the dangers of traditional music extinction is needed, the factors causing extinction and maintenance strategies. This service provides training to the young Dayak Bahau generation in exploring challenges and opportunities for the sustainability of traditional music. Assistance is also carried out in revitalizing traditional arts that are threatened with extinction. This knowledge and skills make traditional music more preserved with an approach that emphasizes the decisions of traditional music owners.